Analisis Implementasi Akad Mudarabah dan Murabahah pada Koperasi Syariah Baitut Tamwil Muhammadiyah Al-Kautsar Makassar (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2026)
This study aims to analyze the implementation of mudarabah and murabahah contracts at the Baitut Tamwil Muhammadiyah (BTM) Al-Kautsar Islamic Cooperative in Makassar and to assess their compliance with Islamic principles and the Islamic Financial Accounting Standards (PSAK Syariah). The research employed a qualitative descriptive approach using in-depth interviews, observation, and documentation. The findings reveal that BTM Al-Kautsar has implemented mudarabah and murabahah contracts in accordance with Islamic principles, as evidenced by valid contract agreements, agreed profit-sharing ratios, and manual transaction recording. The mudarabah contract is applied for profit-sharing financing, while murabahah is more dominant due to its lower risk and stable returns. However, the application of PSAK Syariah remains suboptimal due to limited human resources, the absence of a Sharia supervisory board, and minimal digital accounting systems. These findings suggest the need to enhance Sharia literacy, strengthen internal supervision, and modernize accounting systems to support accountable and sustainable Islamic cooperative governance